Utilization of Distillers Dried Grains with Solubles (DDGS) in Broiler Diets Using a Standardized Nutrient Matrix - Wang, Z.; Cerrate, S.; Coto, C.; Yan, F.; Waldroup, P.W. (International Journal of Poultry Science, 2007)
An experiment was conducted to evaluate different levels of “new generation” distillers dried grains with solubles (DDGS) in broiler diets throughout a 49 d growing period, based a standardized nutrient matrix derived from a composite of literature values. Diets were formulated based on digestible amino acid content to typical U.S. poultry industry standards to contain 0, 5, 10, 15, 20, or 25% DDGS. Each dietary treatment was assigned to four replicate pens of 25 male chicks of a commercial broiler strain. Starter diets (0 to 14 d) were fed as crumbles; grower (14 to 35 d) and finisher (35 to 49 d) diets were fed as pellets. Bulk density (mass/volume) was determined on the crumbled or pelleted feeds. Body weights and feed consumption were determined at 14, 35 and 49 d of age. At the end of the study five representative birds per pen were processed to determine dressing percentage and parts yield. Increasing the DDGS in the diet generally reduced the weight per volume of feed. There were no significant effects of DDGS level on body weight; however chicks fed diets with 25% DDGS consumed significantly more feed and had poorer feed conversion compared to chicks fed the control diet with no DDGS. Birds fed 15 and 25% DDGS had significantly lower dressing percentage than did birds fed the control diet with no DDGS. Birds fed diets with 25% DDGS had significantly lower breast weight when expressed as percentage of live weight but not when expressed as a percentage of the carcass weight, compared to birds fed the control diet with no DDGS. Wing weight as percent of live weight and carcass weight was significantly greater for birds fed diets with 15% DDGS as compared to the control, while wing weight as percent of the carcass was significantly increased for birds fed the diet with 25% DDGS as compared to those fed the control diet with no DDGS. These results indicate that good quality DDGS could be used in broiler diets at levels of 15 to 20% with little adverse effect on live performance but might result in some loss of dressing percentage or breast meat yield.